Pilot External Sector Report. (Policy Papers; Policy Paper ;, 2012)
This Pilot External Sector Report (ESR) provides a multilaterally consistent analysis of the external positions of major world economies. Following the recommendations of thea2011 Triennial Surveillance Reviewaand the Managing Director'saStatement on Strengthening Surveillance, the focus of the analysis has been broadened beyond exchange rates to detailed examinations of current accounts, reserves, capital flows, and external balance sheets. It draws upon the Research Department's past and new methods for assessing current accounts and real exchange rates (see Appendix I), and on previous IMF analytical work on exchange rates, capital flows and measures, and reserves adequacy.